2017
DOI: 10.1007/s12017-017-8462-x
|View full text |Cite
|
Sign up to set email alerts
|

Isorhynchophylline Attenuates MPP+-Induced Apoptosis Through Endoplasmic Reticulum Stress- and Mitochondria-Dependent Pathways in PC12 Cells: Involvement of Antioxidant Activity

Abstract: Endoplasmic reticulum stress (ERS) and mitochondrial dysfunctions are thought to be involved in the dopaminergic neuronal death in Parkinson's disease (PD). In this study, we found that isorhynchophylline (IRN) significantly attenuated 1-methyl-4-phenylpyridinium (MPP)-induced apoptotic cell death and oxidative stress in PC12 cells. IRN markedly reduced MPP-induced-ERS responses, indicative of inositol-requiring enzyme 1 (IRE1) phosphorylation and caspase-12 activation. Furthermore, IRN inhibits MPP-triggered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…Uncaria genus can be found in many ancient TCM formulas treating hypertension, and Uncaria alkaloids are considered as the major bioactive compounds [1, 4,5]. For example, rhyncophylline and isorhyncophylline, two of the most widely studied indole alkaloids from the Uncaria genus, can inhibit the neuronal release of catecholamines, block the conduction between neurons, and indirectly achieve anti-hypertensive effects [7,[38][39][40][41]. Further evidence indicates that the cardiovascular regulation of rhyncophylline and isorhyncophylline comes from direct vasodilation, down-regulation of cardiac output, and reduction of calcium influx [1, 7,42].…”
Section: Discussionmentioning
confidence: 99%
“…Uncaria genus can be found in many ancient TCM formulas treating hypertension, and Uncaria alkaloids are considered as the major bioactive compounds [1, 4,5]. For example, rhyncophylline and isorhyncophylline, two of the most widely studied indole alkaloids from the Uncaria genus, can inhibit the neuronal release of catecholamines, block the conduction between neurons, and indirectly achieve anti-hypertensive effects [7,[38][39][40][41]. Further evidence indicates that the cardiovascular regulation of rhyncophylline and isorhyncophylline comes from direct vasodilation, down-regulation of cardiac output, and reduction of calcium influx [1, 7,42].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, all these findings suggest that Uncaria rhynchophylla display neuroprotective action in protecting neuronal damage through multiple pathways which could be due to the beneficial effect of active compounds as well as the combination effect of those compounds present in Uncaria rhynchophylla. Several studies have reported on the neuroprotective effect of alkaloid in Uncaria rhynchophylla such as hirsutine [187], rhynchophylline [188][189][190][191], and isorhynchophylline [192][193][194][195].…”
Section: Ginseng Ginseng Is a Perennial Herb Belonging To Thementioning
confidence: 99%
“…Paeoniflorin has been reported to reduce MPTP-induced DA cell loss in a dosedependent manner (Zheng et al, 2017). Moreover, isorhynchophylline was found to inhibit the generation of oxidative stress and apoptotic cell death in 1-methyl-4phenylpyridinium (MPP + ) induced PC12 cells (Li et al, 2017). Verbascoside elevates TH-positive cells in PD (Liang and He, 2018).…”
Section: Discussionmentioning
confidence: 99%